Stress response and influencing factors among fever outpatients and children's families during normalisation of the COVID‐19 epidemic: A cross‐sectional study - Lifen Lu; Gui Zheng; Jiangqin He; Hui Wu; Xueqian He; Huajun Yu; Siying Wu; Xiulan Shen (Wiley, 2023)
Abstract Aim To examine the demographic characteristics associated with stress response of fever outpatients and children's families during normalisation of the COVID‐19 epidemic and to examine the relationship between stress response, coping style and resilience. Design Online cross‐sectional study. Methods A total of 541 fever clinic participants from Yiwu, China, were recruited via WeChat from February to November 2021. Online self‐administered questionnaires were used to collect data. Data were analysed using t‐tests, one‐way analyses of variance, Pearson's correlation analyses and multiple linear regression analyses. Results There were apparent physical and emotional responses among the fever outpatients, especially the adult patients. The main coping style was negative coping, and the degree of psychological resilience was low. Income, comorbidities, religious beliefs, tenacity, negative coping and positive coping were independent predictors of stress response.